A new species of the genus Rhachotropis from off Amamioshima Island, northwestern Pacific (Crustacea: Amphipoda: Eusiridae) - Okazaki, Masakuni; Ohtsuka, Susumu; Tomikawa, Ko (Zootaxa, 2020)
A new species of the eusirid amphipod, Rhachotropis reiwa is described from off Amamioshima Island, northwestern Pacific. The new species differs from its congeners in having large eyes, the middorsal tooth on pereonite 7, pleonite 3 and urosomite 1 without middorsal and dorsolateral teeth, the basis of pereopod 5 strongly produced posteriorly, and pereopod 6 with the triangular basis. A key to the species of Rhachotropis from Japanese and adjacent waters is provided. Additionally, a nucleotide sequence of mitochondrial cytochrome c oxidase subunit I from its holotype was determined for the future study.